1999
DOI: 10.1093/emboj/18.23.6682
|View full text |Cite
|
Sign up to set email alerts
|

An N-terminal nuclear export signal is required for the nucleocytoplasmic shuttling of Ikappa Balpha

Abstract: The potent transcriptional activities of Rel/NF-κB proteins are regulated in the cytoplasm and nucleus by the inhibitor, IκBα. The mechanism, by which IκBα can either sequester NF-κB in the cytoplasm or act as a nuclear post-induction repressor of NF-κB, is uncertain. We find that IκBα shuttles continuously between the nucleus and cytoplasm. This shuttling requires a previously unidentified CRM1-dependent nuclear export signal (NES) located within the N-terminal domain of IκBα at amino acids 45-55. Deletion or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
220
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(238 citation statements)
references
References 42 publications
18
220
0
Order By: Relevance
“…endogenous NF-kB, whose cytoplasmic localization requires active CRM1-dependent export from the nucleus (Johnson et al, 1999), confirmed the effective blockage of CRM1 in these cells. In line with the lack of LMB responsiveness, the fraction of Borealin localized in the nucleus did not undergo relocation to the cytoplasm when coexpressed with YFP-CRM1 ( Figure 3c).…”
Section: Resultssupporting
confidence: 56%
“…endogenous NF-kB, whose cytoplasmic localization requires active CRM1-dependent export from the nucleus (Johnson et al, 1999), confirmed the effective blockage of CRM1 in these cells. In line with the lack of LMB responsiveness, the fraction of Borealin localized in the nucleus did not undergo relocation to the cytoplasm when coexpressed with YFP-CRM1 ( Figure 3c).…”
Section: Resultssupporting
confidence: 56%
“…14 The subcellular location of NF-kB is controlled by a family of inhibitory proteins, IkBs, such as IkBa, which bind NF-kB to maintain the cytoplasmic localization of NF-kB in unstimulated cells. 14 Exposure of cells to a variety of extracellular stimuli leads to the rapid phosphorylation, ubiquitination, and ultimately proteolytic degradation of IkBa, which allows the nuclear translocation of NF-kB where it binds to DNA and regulates gene transcription.…”
Section: Resultsmentioning
confidence: 99%
“…14 Exposure of cells to a variety of extracellular stimuli leads to the rapid phosphorylation, ubiquitination, and ultimately proteolytic degradation of IkBa, which allows the nuclear translocation of NF-kB where it binds to DNA and regulates gene transcription. 11,14 Both LPS and TNFa induce NF-kB transcriptional activity through the degradation of the inhibitor IkB. These external signals act through their respective receptors to activate the IkB kinase (IKK) complex, which contains the catalytic subunits IKKa and IKKb, and the regulatory subunit IKKg/ NEMO.…”
Section: Resultsmentioning
confidence: 99%
“…IkB-a is a physiological ligand of NF-kB in the cytoplasm, whose phosphorylation permits the liberation and migration of NF-kB into the nucleus, where NF-kB plays its transcriptional role, upregulating the expression of antiapoptotic proteins. 7,[27][28][29][30] In MALT lymphoma, deregulation of the expression of MALT1 gene due to chromosomal translocations t(11;18)(q21; q21) and t(14;18)(q32;q21) seems to be one of the main pathogenic mechanisms leading to reduced apoptotic activity. 12,15,22,[31][32][33] In contrast to what has been described in gastric MALT lymphomas, our results did not indicate the presence of t (11;18).…”
Section: Discussionmentioning
confidence: 99%